Apoplexy inside a giant medial sphenoid wing meningothelial (Grade I) meningioma: An extremely rare but a potentially dangerous complication - Gajbhiye, Sanjog; Gosal, Jaskaran; Pandey, Satyadeo; Das, Kuntal (Asian Journal of Neurosurgery, 2019)
Hemorrhage associated with meningiomas is extremely rare and most commonly occurs in convexity meningiomas of higher grade or the angioblastic variety. Moreover, bleeding associated with a meningioma usually occurs in the form of a subdural hematoma or subarachnoid hemorrhage. We report a case of giant left medial sphenoid wing meningioma with histopathological diagnosis of a meningothelial type with apoplexy. A 54-year-old female presented with clinical features suggestive of apoplexy. Her neuroimaging demonstrated a large left medial sphenoid wing meningioma with features suggestive of an intratumoral bleed with mass effect. Gross total excision of the tumor was done with the good postoperative outcome. The biopsy came out to be Grade I meningothelial meningioma. Apoplexy in meningiomas is extremely rare with a reported incidence of 0.5%–2.4%, especially in a nonconvexity meningioma with histopathological diagnosis of meningothelial variety. Early diagnosis and prompt surgical intervention are critical as meningiomas associated with apoplexy are associated with high morbidity.
Keywords: Intratumoral hemorrhage; meningioma; meningothelial; nonconvexity; sphenoid wing